(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Study of floristic composition of a place, whether natural or man-made, at periodic intervalsproves essential in assessment of biodiversity in spatial and temporal scales since many of theconstituent species perceive various degrees of threats of extinction. In view of this, the present authorprioritized identification and documentation of various plants inDeoghar District of Jharkhand Statewhich is located at 24.48°N and 86.7°E with an average elevation of 254 meters (833 feet). The areaproves to be the very important resource base in terms of biodiversity and economy of the region. For itslong term sustainability and species conservation proper sustainable management practices andstrategies need to be developed.